2021
DOI: 10.1155/2021/1213978
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Design Model of Urban Leisure Sports Public Facilities Based on Big Data and Machine Vision

Abstract: Sports facilities are the material basis for people to participate in physical exercise. The construction of facilities is conducive to improving people’s health and their expectations for a happy life. Sports facilities are part of the infrastructure. The reasonable layout of sports facilities is conducive to shortening the gap between urban and rural areas, achieving common economic prosperity, and promoting social harmony and unity. Public sports facilities are of great significance to urban construction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Some scholars also integrated Fourier series and discrete function into allocation and management [ 9 ] and found that classifying public sport facility resources can improve the accuracy of allocation and management and shorten the processing time of public sport facility resources. In short, domestic scholars have integrated the spatial spectrum estimation method, Fourier series [ 10 ], spatial spectrum estimation method, and other comprehensive analysis methods into the analysis process [ 11 ], which can reduce the data dispersion and improve the accuracy of resource allocation and management results of public sport facilities [ 12 ]. Therefore, using the spatial spectrum estimation method to manage public sport facilities resources can not only realize the comprehensive allocation of resources but also improve the management level and realize multifactor analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars also integrated Fourier series and discrete function into allocation and management [ 9 ] and found that classifying public sport facility resources can improve the accuracy of allocation and management and shorten the processing time of public sport facility resources. In short, domestic scholars have integrated the spatial spectrum estimation method, Fourier series [ 10 ], spatial spectrum estimation method, and other comprehensive analysis methods into the analysis process [ 11 ], which can reduce the data dispersion and improve the accuracy of resource allocation and management results of public sport facilities [ 12 ]. Therefore, using the spatial spectrum estimation method to manage public sport facilities resources can not only realize the comprehensive allocation of resources but also improve the management level and realize multifactor analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the SC3 model can predict the risk relationship between climate change and physical and mental health, which has an important role for people to improve physical and mental health and reduce the impact of climate on physical and mental health. Liu and Zhang [ 33 ] also believe that reasonable sports facilities will improve people's well-being; it will also improve people's physical and mental health. However, the layout of sports facilities is unreasonable and the gap between urban and rural areas is large.…”
Section: Related Workmentioning
confidence: 99%
“…The deepening of China's reform and opening up and the continuous improvement of the market economic system, on the one hand, has improved people's living conditions and quality of life, while the increase in the amount of leisure time has changed people's leisure and entertainment structure and lifestyle [8][9]. On the other hand, people's work pressure is increasing, life becomes tense, nutrition appears to be in excess, and the living environment is damaged.…”
Section: Introductionmentioning
confidence: 99%